Correlação entre sonolência diurna, bruxismo e alterações emocionais em pacientes com dor nos músculos mastigatórios - Oliveira, Vinicius Silveira de [UNESP] (2017)
Sleep is a physiological state with influence on the physical, psychological and social conditions of the individual. The alteration of sleep may make individuals more susceptible to the development of chronic pain and systemic disorders. Sleep bruxism (BS) is associated with micro arousers, and differs from bruxism in wakefulness (BV), but both are associated with the presence of pain in a part of the population. The objective of this study was to evaluate the correlation of Daytime Excessive Drowsiness with bruxism (BS and BV), Emotional Stress, Anxiety and Depression in patients with TMD of the Nucleus of Diagnosis and Treatment of Temporomandibular Disorders (NDTDTMs). For this, we selected patients with TMD diagnosed with CRD (Research Diagnostic Criteria), from the clinic of the NDTDTMs of FOA (UNESP). A total of 74 patients with low risk of obstructive sleep apnea or hypopnea (OSAHS) identified by the Berlin questionnaire were included (Netzer et al., 1999) - (Annex E). Emotional changes were assessed using the Lipp Adult Stress Symptom Inventory (ISSL), Beck Depression (BDI) and Anxiety Assessment (BAI). Excessive Daytime Sleepiness was measured through the Epworth Sleepiness questionnaire, and Bruxism through the adapted Pintado questionnaire. After data collection, the patients were divided into two groups: Drowsiness (G1) and Sleepiness (G2). The results were submitted to statistical analysis using SPSS 20.0 (SPSS, Chicago, IL, USA) with alpha (α) = 0.05, applying the Spearman correlation test to verify the correlation between the variables. The results showed that most of the patients did not present excessive daytime sleepiness (87.84%), and that there was no correlation between daytime sleepiness and none of the types of bruxisms analyzed and emotional changes. In view of this, it is concluded that excessive daytime sleepiness is not correlated with bruxism (BV + BS) and the emotional changes investigated